2018
DOI: 10.1038/s41598-018-23920-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphatidylserine and Cholesterol on Membrane-mediated Fibril Formation by the N-terminal Amyloidogenic Fragment of Apolipoprotein A-I

Abstract: Here, we examined the effects of phosphatidylserine (PS) and cholesterol on the fibril-forming properties of the N-terminal 1‒83 fragment of an amyloidogenic G26R variant of apoA-I bound to small unilamellar vesicles. A thioflavin T fluorescence assay together with microscopic observations showed that PS significantly retards the nucleation step in fibril formation by apoA-I 1‒83/G26R, whereas cholesterol slightly enhances fibril formation. Circular dichroism analyses demonstrated that PS facilitates a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 89 publications
(106 reference statements)
1
17
0
Order By: Relevance
“…S9). Because ␣-helix formation of the amyloidogenic segments upon lipid binding strongly inhibits ␤-transition and fibril formation by the N-terminal fragment of apoA-I (18,19), it is likely that the second amyloidogenic segment containing residues 50 -58 is not available for fibril formation of apoA-I 1-83/G26R on the membrane surface (19). The inhibitory effect of the deletion of residues 32-40 on the kinetics of nucleation and fibril growth (Fig.…”
Section: Aggregation and Fibril Formation Mechanism Of Apoa-i Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S9). Because ␣-helix formation of the amyloidogenic segments upon lipid binding strongly inhibits ␤-transition and fibril formation by the N-terminal fragment of apoA-I (18,19), it is likely that the second amyloidogenic segment containing residues 50 -58 is not available for fibril formation of apoA-I 1-83/G26R on the membrane surface (19). The inhibitory effect of the deletion of residues 32-40 on the kinetics of nucleation and fibril growth (Fig.…”
Section: Aggregation and Fibril Formation Mechanism Of Apoa-i Discussionmentioning
confidence: 99%
“…Studies of synthetic apoA-I fragment peptides demonstrated that the peptides containing either the first (residues 14 -22) or the second (residues 50 -58) amyloidogenic segment have the ability to form amyloid-like fibrils with ␤-transition, whereas the peptide only containing residues 69 -72 does not form fibrils at neutral pH (13,14). Interestingly, because the two major amyloidogenic segments (residues 14 -22 and 50 -58) overlap with the hydrophobic ␣-helix-forming regions upon lipid binding (15,16), lipid membrane environments significantly affect the fibril-forming properties of the N-terminal fragments or peptides of apoA-I (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid composition of cell membranes is thought to modulate the interactions of amyloidogenic proteins with membranes. For instance, it is well known that negatively charged phosphatidylserine (PS) strongly influences the kinetics of aggregation and fibril formation of many amyloidogenic proteins including apoA-I [23,[28][29][30][31]. In contrast, with the exception of phosphatidylcholine (PC), little is known about the effects of zwitterionic phospholipids (PLs) such as phosphatidylethanolamine (PE) and sphingomyelin (SM), on the membrane-mediated aggregation and fibrillation properties of amyloidogenic proteins [32][33][34][35].…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Heats of binding of apoA-I 1-83/G26R to SUV were measured with a VP-ITC instruments (Malvern) at 25 °C as described previously [24,31]. The SUV suspension was placed in the sample cell (1.33 ml) and titrated with 10 l aliquots of the apoA-I Author Manuscript equilibrium and a finite number of discrete, equivalent, and non-interacting binding sites on the lipid surface, which is mathematically equivalent to the one-site or Langmuir binding model [41][42][43].…”
Section: Isothermal Titration Calorimetry (Itc) Measurementsmentioning
confidence: 99%